STRATEGI PENINGKATAN DAYA SAING UMKM PUJASERA PAKUALAMAN SHIFT SORE MELALUI INOVASI DAN KOLABORASI: MENUJU KEUNGGULAN KOMPETITIF DI PASAR - Listyawati, Reni; Prastyatini, Sri Lestari Yuli; Chaerunisak, Uum Helmina; Safira, Maghfirotus; Aini, Syarivatul; Kharisma, Enggar Dwi (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2024)
This community service project aims to enhance the competitiveness and operational efficiency of Micro, Small, and Medium Enterprises (MSMEs) in the Pujasera Pakualaman Night Shift Unit, focusing on Lesehan Pakualaman Mbak Nila, Warung Anugerah, and Bakso Pak Riyanto. Through initial surveys and consultations with MSME vendors, several challenges, such as competition with similar products, payment issues, absence in e-commerce channels, and weather impacts, were identified. Implemented solutions include developing innovative menus, applying the Quick Response Code Indonesian Standard (QRIS) payment system, and integrating online ordering services. Training and empowerment processes were conducted to improve vendors' understanding of product innovation, digital payment technology, and e-commerce operational management. Implementing these solutions is expected to bring positive changes that strengthen the competitiveness and operational efficiency of MSMEs in Pujasera Pakualaman and contribute to local economic growth.